2009
DOI: 10.1017/s1751731109004200
|View full text |Cite
|
Sign up to set email alerts
|

Intake, growth and carcass traits in male progeny of sires differing in genetic merit for beef production

Abstract: Validation of economic indexes under a controlled experimental environment, can aid in their acceptance and use as breeding tools to increase herd profitability. The objective of this study was to compare intake, growth and carcass traits in bull and steer progeny of high and low ranking sires, for genetic merit in an economic index. The Beef Carcass Index (BCI; expressed in euro (h) and based on weaning weight, feed intake, carcass weight, carcass conformation and fat scores) was generated by the Irish Cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
8
31
0
Order By: Relevance
“…There was no further divergence during the second winter. This pattern of LW change over time is almost identical to that observed by Campion et al (2009a) and similar to that reported by Clarke et al (2009), who studied progeny from Irish beef cows. Unlike previously (Campion et al, 2009a), where breed type by genetic merit interactions for live weights were detected no such interactions were detected in this study, indicating that EPD CWT effects were consistent across the two breed types.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There was no further divergence during the second winter. This pattern of LW change over time is almost identical to that observed by Campion et al (2009a) and similar to that reported by Clarke et al (2009), who studied progeny from Irish beef cows. Unlike previously (Campion et al, 2009a), where breed type by genetic merit interactions for live weights were detected no such interactions were detected in this study, indicating that EPD CWT effects were consistent across the two breed types.…”
Section: Discussionsupporting
confidence: 88%
“…However, slaughter weight per day of age was significantly greater for H. Campion et al (2009a) also found that slaughter weight per day of age was greater for high EPD CWT animals even though the only significant difference in LW gain was during the first grazing season. Thus, the results of all three studies (Clarke et al, 2009;Campion et al, 2009a and this study) that have evaluated the Irish beef genetic evaluation system agree that genetic merit for growth, as measured by EPD CWT, is more strongly expressed early in life than during finishing.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The efficacy of this economic index was first examined under a controlled environment in contrasting production systems, and results showed that the observed differences in profitability of progeny of sires differing in BCI were in good agreement with the expected values (Clarke et al, 2009). Furthermore, for each unit increase in sire EPD for weaning weight, DM intake, carcass weight, carcass conformation score and carcass fat score, progeny performance increased for each of the respective traits by 1.0, 1.1, 1.3 kg, 0.9 (scale 1 to 15) and 1.0 (scale 1 to 15); none of which differed from the theoretical expectation of unity.…”
Section: Introductionmentioning
confidence: 81%
“…Bulls were individually offered a barley-based concentrate diet ad libitum using Calan-Broadbent gates (American Calan, Northwood, New Hampshire, USA) until slaughter on 26 June 2006 as described by Clarke et al (2009). Steers were offered grass silage ad libitum and a concentrate supplement for most of the winter, and were turned out to pasture on 18 April.…”
Section: Methodsmentioning
confidence: 99%